Halalan Thayyiban fi Al-Qur’an ‘inda Wahbah Al-Zuhaily fi Tafsir Al-Munir - A Fadly Rahman Akbar; Mahmud Rifaannudin; Siti Nurhasanah (Studia Quranika, 2022)
Halal food and thayyib, is food that is not prohibited by religion and does not harm the body. The words halal and thayyib are found in Surah Al-Maidah verse 88 which are interpreted by several tafsir scholars, such as Ahmad Mustafa al-Maragi in Tafsir al-Maragi, Fahri Ar-Razi in Tafsir Mafatihul Ghaib, Muhammad Abduh in Tafsir Manar, namely halal food and thayyib which consists of various foods, including livestock, which are useful for the body, do not damage, are not disgusting, delicious, do not expire and do not contradict Allah's orders. Eating halal and thayyib food is highly recommended by Islam because it will affect the health of the body and soul, more importantly it can affect a person's morals and beliefs, and cause prayer and worship to come true. With so many interpretations of halal food and thayyib, researchers want to reveal a reliable narrative using Wahbah Az-Zuhaili's Tafsir Al-Munir Book. Based on the above background, the researcher tries to find out Halal Food, Thayyib, according to Wahbah Az-Zuhaili in his interpretation of Al-Munir with a thematic approach which sets each verse in its place. In this study, the method used is the descriptive method to discuss the life journey of Wahbah Az-Zuhaili and information about Thayyib Halal food and analysis methods to study the history and background of Wahbah Az-Zuhaili's thought and the final fruit of his thoughts and opinions of the Mufassirs. Halal food and Thayyib in the Koran. Meanwhile, the data sources used are primary data in the form of Al-Qur'an exegesis literature and several books, to assist in discovering Wahbah Az-Zuhaili's thoughts. And researchers also use secondary data from existing primary data sources as support. This study uses a thematic approach, namely interpreting the verses of the Qur'an by collecting verses that have the same meaning and purpose. I hope that this research will be useful for writers in particular and readers in general and that there will be further studies that are better and more useful.